Relationship between interferon production and interferon messenger RNA synthesis in human fibroblasts. - Raj, N B (1977)
Poly(A) containing mRNA prepared from poly(rI)-poly(rC)-induced human fibroblasts stimulated [14C]leucine incorporation into protein in wheat germ cell-free extracts. For the translation of interferon mRNA into a biologically active product, the presence of spermine was essential. The protein synthesized in vitro fulfilled the criteria for human interferon--namely, its antiviral activity was species specific, and its activity was completely neutralized by antiserum to human fibroblast interferon. The amount of interferon synthesized in human fibroblasts induced by poly(rI)-poly(rC) (normal induction) and poly(rI)-poly(rC) in the presence of cycloheximide (superinduction) was compared to the amount of translatable interferon mRNA both in the wheat germ cell-free system and the Xenopus oöcyte system. Although the production of interferon after the termination of transcription by actinomycin D was markedly increased in superinduced cells, the measurable amount of interferon mRNA as assayed in the oöcyte system was only slightly higher in superinduced cells than in cells induced with poly(rI)-poly(rC) alone. When compared in the wheat germ cell-free system, however, the translational product of mRNA preparation from cells induced with poly(rI)-poly(rC) alone was inactive while that from superinduced cells was active.